Multidisciplinary cancer care in Spain, or when the function creates the organ: qualitative interview study - Borràs Josep M; Prades Joan (BMC, 2011)
Abstract Background The Spanish National Health System recognised multidisciplinary care as a health priority in 2006, when a national strategy for promoting quality in cancer care was first published. This institutional effort is being implemented on a co-operative basis within the context of Spain's decentralised health care system, so a high degree of variability is to be expected. This study was aimed to explore the views of professionals working with multidisciplinary cancer teams and identify which barriers to effective team work should be considered to ensure implementation of health policy. Methods Qualitative interview study with semi-structured, one-to-one interviews. Data were examined inductively, using content analysis to generate categories and an explanatory framework. 39 professionals performing their tasks, wholly or in part, in different multidisciplinary cancer teams were interviewed. The breakdown of participants' medical specialisations was as follows: medical oncologists (n = 10); radiation oncologists (n = 8); surgeons (n = 7); pathologists or radiologists (n = 6); oncology nurses (n = 5); and others (n = 3). Results Teams could be classified into three models of professional co-operation in multidisciplinary cancer care, namely, advisory committee, formal co-adaptation and integrated care process. The following barriers to implementation were posed: existence of different gateways for the same patient profile; variability in development and use of clinical protocols and guidelines; role of the hospital executive board; outcomes assessment; and the recording and documenting of clinical decisions in a multidisciplinary team setting. All these play a key role in the development of cancer teams and their ability to improve quality of care. Conclusion Cancer team development results from an specific adaptation to the hospital environment. Nevertheless, health policy plays an important role in promoting an organisational approach that changes the way in which professionals develop their clinical practice.